2010
DOI: 10.1124/jpet.109.164376
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Heart Failure by a Methanocarba Derivative of Adenosine Monophosphate: Implication for a Role of Cardiac Purinergic P2X Receptors

Abstract: Evidence is accumulating to support a potentially important role for purinergic (P2X) receptors in heart failure (HF). We tested the hypothesis that a hydrolysis-resistant nucleotide analog with agonist activity at myocardial P2X receptors (P2XRs) improves the systolic HF phenotype in mouse and dog models. We developed a hydrolysis-resistant adenosine monophosphate derivative, (1ЈS,2R,3S,4ЈR,5ЈS)-4-(6-amino-2-chloro-9H-purin-9-yl)-1-[phosphoryloxymethyl] bicycle[3.1.0]hexane-2,3-diol) (MRS2339), with agonist a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…We found that a non-hydrolyzable phosphonate analog of AMP could activate hA 1 R. Interestingly, other ectonucleotidase-resistant phosphonate analogs of AMP reportedly activate P2X receptors and have cardioprotective activity in vivo (47,48). Although it was suggested that the cardioprotective effects of these AMP analogs were due to P2X activation, P2X involvement was never directly tested in vivo with antagonists or knock-out mice.…”
Section: Discussionmentioning
confidence: 97%
“…We found that a non-hydrolyzable phosphonate analog of AMP could activate hA 1 R. Interestingly, other ectonucleotidase-resistant phosphonate analogs of AMP reportedly activate P2X receptors and have cardioprotective activity in vivo (47,48). Although it was suggested that the cardioprotective effects of these AMP analogs were due to P2X activation, P2X involvement was never directly tested in vivo with antagonists or knock-out mice.…”
Section: Discussionmentioning
confidence: 97%
“…P2XR activation protected the heart in heart failure models [481,482]. A beneficial effect of MRS2339, a P2XR agonist in heart failure was demonstrated; it was identical to that produced by cardiac myocyte-specific over-expression of the P2X4R [483]. The improvement was associated with the preservation of left ventricular wall thickness in both systole and diastole in post-infarct mice and calsequestrin (CSQ) over-expression mice with cardiac-specific P2X4R overexpression and decreased left ventricular chamber size in CSQ mice with heart failure and dogs with pacing-induced heart failure [483].…”
Section: Pathophysiology and Therapeutic Potentialmentioning
confidence: 99%
“…UTP, but not ATP, caused hypertrophic growth in neonatal cardiomyocytes [736]. Overexpression of human P2X4R in ventricular myocytes of a transgenic mouse increased basal cardiac contractility without cardiac hypertrophy or failure [274] and activation with a P2X4R agonist had beneficial effects [483]. Deletion of the P2Y4R gene in mice lowered exercise capacity and reduced myocardial hypertrophy [737].…”
Section: Cardiac Hypertrophymentioning
confidence: 99%
“…Experiments that measure the displacement of [ 35 S]ATP␥S from rP2X4Rs also indicated that ATP is the most potent agonist, followed by ATP␥S, 2-meSATP, and ␣␤-meATP . A methanocarba derivative of AMP, 1ЈS,2R,3S,4ЈR,5ЈS)-4-(6-amino-2-chloro-9H-purin-9-yl)-1-[phosphoryloxymethyl] bicycle[3.1.0]hexane-2,3-diol) (MRS2339), has been found to act as a potent agonist of heart purinergic receptors; the authors suggested that this compound could be a P2X4R agonist (Zhou et al, 2010).…”
Section: Activation and Regulation Of P2xrsmentioning
confidence: 99%